2021
DOI: 10.29244/jai.2021.9.2.143-153
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Efisiensi Usahatani Padi di Jawa dan Luar Jawa, Kajian Prospek Peningkatan Produksi Padi Nasional

Abstract: Rice can grow in almost all of the islands in Indonesia, but 57 per cent of it was produced in Java, which is less than 10 per cent of the national area in Indonesia. To anticipate the increasing need for rice consumption, it is important to study the prospects for increasing national rice production, especially by utilizing the potential of agricultural land outside Java island. The purpose of this study was to identify the prospects for the development of national rice, especially outside Java island, from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
2
5
0
9
Order By: Relevance
“…Oleh karena itu petani dengan lahan non milik akan berusaha untuk menghasilkan produksi semaksimal mungkin. Pada penelitian Rivanda et al (2015), Khotimah dan Nurmalina (2012) dan Hilalullaily et al (2021)…”
Section: Faktor-faktor Yang Memengaruhi Nilai Efisiensi Teknisunclassified
“…Oleh karena itu petani dengan lahan non milik akan berusaha untuk menghasilkan produksi semaksimal mungkin. Pada penelitian Rivanda et al (2015), Khotimah dan Nurmalina (2012) dan Hilalullaily et al (2021)…”
Section: Faktor-faktor Yang Memengaruhi Nilai Efisiensi Teknisunclassified
“…Hal ini dikarenakan adanya tanggungan biaya yang dibebankan kepada petani penggarap untuk membayar biaya sewa yang cenderung lebih tinggi dibandingkan petani pemilik karena adanya biaya biaya tambahan berupa biaya sewa lahan. Hasil tersebut sama dengan penelitian (Ulfah et al,2018), (Hilalullaily et al, 2021), namun kontradiksi dengan hasil penelitian yang dilakukan oleh (Syahputra, 2022).…”
Section: Faktor-faktor Yang Mempengaruhi Efisiensi Teknisunclassified
“…Rahayu (2019) reported that rice production has an inverse relationship with imports: the higher the import, the lower the production. Meanwhile, Hilalullaily et al (2021) suggested that the increase in productivity and production was due to an increase in agricultural input use and agricultural land area.…”
Section: Introductionmentioning
confidence: 99%